P-036 Analysis of semen cryopreservation in a cohort of cancer patients. (30th June 2022) - Sileo, F.G; Melli, B; Morini, D; Daolio, J; Nicoli, A; Valli, B; Di Girolamo, R.A.M; Capodanno, F; Spaggiari, G; Aguzzoli, L; Santi, D; Villani, M.T
Abstract: Study question: To investigate the possible correlation between different types of cancer and sperm quality in patients preserving their fertility and evaluate the reproductive outcomes of patients Summary answer: Testicular cancer was associated with lower sperm volumes (p = 0.041), lower total sperm concentration (p = 0.009) and oligozoospermia (p < 0.001) compared to other cancers. What is known already: The advancement in cancer treatments over the years frequently allowed a remission in most young patients. In males, spermatogonia are sensitive to chemotherapy and radiotherapy, causing an impairment of sperm production and competence. Moreover, up to two-thirds of patients with cancer have impaired semen parameters before any treatment but findings on whether and how specific types of malignancies can alter them remains heterogeneous. Today the advancement of Assisted Reproductive Technologies (ART) made male fertility preservation widely available, therefore counselling and sperm banking should be offered to all men in reproductive age with a diagnosis of cancer before any treatment. Study design, size, duration: This was an observational cohort study conducted on cancer patients that underwent fertility preservation at the Center of reproductive Medicine and Surgery "P. Bertocchi" at the Department of Obstetrics and Gynecology in AUSL-IRCCS of Reggio Emilia, Italy between 2007 and 2018. The participation to the study was retrospectively proposed to all patients submitted to fertility preservation counselling from January 1st 2007 to March 28th 2018, and prospectively from March 29th 2018 to December 31st 2018. Participants/materials, setting, methods: Semen parameters regarding volume, concentration, motility, and morphology were assessed according to the WHO criteria of 2010 in semen samples collected before any cancer treatment. Based on the macroscopic and microscopic evaluation of each sample, all those with at least cryptozoospermia were frozen. We also evaluated the reproductive outcomes of patients seeking a pregnancy with sperm frozen before cancer treatments. Semen parameters and pregnancy outcomes were compared between testicular versus other cancers. Main results and the role of chance: During the study period, 329 patients were included with a mean age at enrollment of 32.7 ± 8.6 years. A successful cryopreservation was achieved in 94.5% of cases; the cryopreservation failed in 5.5% of cases, due to azoospermia or missed delivery samples. More than half of the cryopreservations were performed in patients affected by testicular cancer (53.3%), followed by those affected by Hodgkin (19.3%) and non-Hodgkin Lymphoma (13.5%), reflecting the increased incidence of these cancer histotypes in the age group of 20-40 years. Testicular cancer was associated with lower sperm volumes (p = 0.041) and lower total sperm concentration (p = 0.009) compared to other cancers. No difference was observed about sperm motility and morphology, while oligozoospermia was significantly more frequent in men with testicular cancer (p < 0.001). In the cohort, the 8.4% of patients thawed their samples; the usage rate and the embryo transfer rate were significantly higher (p = 0.04) among those with a testicular cancer, while pregnancy and livebirth rates did not differ between the two groups. Limitations, reasons for caution: Relevant limitations of the study included: the absence of a follow-up on fertility status after cancer remission, missing data about spontaneous pregnancies, and information on the seminal status of each patient before cancer diagnosis, precluding any etiopathological consideration between neoplastic pathology and seminal parameters. Wider implications of the findings: Male fertility preservation is feasible, easy to be performed, non-invasive and does not delay cancer treatments. Men affected by testicular cancer had worse semen parameters at cryopreservation, but pregnancy and livebirth rates were similar to those achieved by men with other cancers and similar to those achieved with fresh sperm. Trial registration number: not applicable